EFEKTIVITAS MEDIA BUKU PICTURE EXCHANGE COMMUNICATION SYSTEM UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI EKSPRESIF PADA ANAK DENGAN GANGGUAN EMOSI DAN PERILAKU - Novita, Suci; Marlina, Marlina; Damri, Damri; Nasri, Yosa Yulia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Students with emotional and behavioral disorders generally experience difficulties in socializing, communicating, thinking processes, and have behaviors that can make the environment uncomfortable. Based on the results of the assessment that has been carried out in an inclusive school, there is one student with emotional and behavioral disorders who shows difficulties in expressive communication skills in class. The results of the identification and assessment that the researcher conducted are based on the identification instrument for children with special needs and expressive communication assessment. The purpose of this study is to test the effectiveness of the PECS book media in improving expressive communication skills in students with emotional and behavioral disorders. The study used a single subject research form with an A-B-A design. The research subject is one person with the target behavior of students with emotional and behavioral disorders who can improve their expressive communication skills. The results of the study show an increase in expressive communication skills in students after being given the PECS book media. It is recommended that teachers can use the PECS book media as a learning medium that aims to help students improve their expressive communication skills.